The female athlete triad - Weiss Kelly, A. K.; Hecht, S. (Pediatrics, 2016)
The number of girls participating in sports has increased significantly since the introduction of Title XI in 1972. As a result, more girls have been able to experience the social, educational, and health-related benefits of sports participation. However, there are risks associated with sports participation, including the female athlete triad. The triad was originally recognized as the interrelationship of amenorrhea, osteoporosis, and disordered eating, but our understanding has evolved to recognize that each of the components of the triad exists on a spectrum from optimal health to disease. The triad occurs when energy intake does not adequately compensate for exercise-related energy expenditure, leading to adverse effects on reproductive, bone, and cardiovascular health. Athletes can present with a single component or any combination of the components. The triad can have a more significant effect on the health of adolescent athletes than on adults because adolescence is a critical time for bone mass accumulation. This report outlines the current state of knowledge on the epidemiology, diagnosis, and treatment of the triad conditions.